Bicycle Tourism Development Model to Increase Community Income in Tourism Villages the Case of Burai Ecotourism Village, Ogan Ilir Regency - Muhammad Iqbal Djohan; Sulastri Sulastri; Marlina Widiyanti; Abdul Rahman (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Sports tourism is booming today fueled by the increasing awareness of health and fitness around the world, resulting in a wide array of sporting events and outdoor recreational activities. One of them is Bicycle tourism, which is developing into one of the increasingly recognized tourist activities. Although it is well-known globally, it has not been packaged well in tourist villages, this potential has not been adequately utilized by the people of tourism villages, furthermore, the completeness of data on the potential of tourism products is also an obstacle to the development of Bicycle tourism product models. This research aims to develop bicycle tourism itinerary products based on tourism village potential prepared with local communities in the Burai tourism village. This research uses a combination method or mixed method with a sequential explanatory design, while the data analysis used is the Miles and Huberman model steps which are interactive, namely, data collection, data reduction, data display, and conclusion. Then the population is tourists visiting tourist villages and the resource persons/informants are: (1) Community Drivers of the tourism sector; (2) Local authorities; and (3) tourists. Data was obtained quantitatively and sampled using the Random Sampling technique. The result of this research is the creation of a light-category and medium-category Bicycle tourism development model and becomes a packaging solution for tourist bicycle products in tourist villages that increase people's income in tourist villages. This research contributes to the form of diversification of tourism products in tourism villages, so that natural tourism attractions, cultural tourism and artificial tourism can collaborate into products that have been made so that the community and further research can be developed on the potential absorption of informal labour that may arise based on needs found in the field.